Evaluation of online videos to engage viewers and support decision-making for COVID-19 vaccination: how narratives and race/ethnicity enhance viewer experiences - Schuh, Holly B.; Rimal, Rajiv N.; Breiman, Robert F.; Orton, Peter Z.; Dudley, Matthew Z.; Kao, Lee-Sien; Sargent, Rikki H.; Laurie, Shaelyn; Weakland, Leo F.; Lavery, James V.; Orenstein, Walter A.; Brewer, Janesse; et al. (Frontiers in Public Health, 2023)
Background Vaccine hesitancy has hampered the control of COVID-19 and other vaccine-preventable diseases. Methods We conducted a national internet-based, quasi-experimental study to evaluate COVID-19 vaccine informational videos. Participants received an informational animated video paired with the randomized assignment of (1) a credible source (differing race/ethnicity) and (2) sequencing of a personal narrative before or after the video addressing their primary vaccine concern. We examined viewing time and asked video evaluation questions to those who viewed the full video. Results Among 14,235 participants, 2,422 (17.0%) viewed the full video. Those who viewed a personal story first (concern video second) were 10 times more likely to view the full video (p < 0.01). Respondent–provider race/ethnicity congruence was associated with increased odds of viewing the full video (aOR: 1.89, p < 0.01). Most viewers rated the informational video(s) to be helpful, easy to understand, trustworthy, and likely to impact others' vaccine decisions, with differences by demographics and also vaccine intentions and concerns. Conclusion Using peer-delivered, personal narrative, and/or racially congruent credible sources to introduce and deliver vaccine safety information may improve the openness of vaccine message recipients to messages and engagement.